Lenvatinib and other tyrosine kinase inhibitors for the treatment of radioiodine refractory, advanced, and progressive thyroid cancer - Lorusso, Loredana (Onco Targets Ther, 2016)
Lenvatinib is a small oral molecule able to inhibit three of the extracellular and intracellular molecules involved in the modulation of angiogenesis and lymphangiogenesis: vascular endothelial growth factor receptor 1–3, fibroblast growth factor receptor 1–4, and platelet-derived growth factor receptor alpha. Since it is also able to inhibit the REarranged during Transfection oncogene and the protooncogene c-KIT, this drug can also be used to control tumor cell proliferation. The maximum tolerated dose, as demonstrated in Phase I studies, is 25 mg daily. The drug is rapidly absorbed with maximum concentrations achieved within 3 and 5 hours after administration in fasting and nonfasting treated patients, respectively. The most common adverse events, reported in Phase I study and confirmed in the subsequent Phase II and III studies, are hypertension, proteinuria, and gastrointestinal symptoms such as nausea, diarrhea, and stomatitis. In Phase I studies, efficacy of lenvatinib in solid tumors was demonstrated, and these encouraging results have led to the development of a Phase II study using lenvatinib in advance radioiodine-refractory differentiated thyroid cancer (DTCs) patients. Since an overall response rate of 50% was reported, this study also confirmed the efficacy of lenvatinib in DTCs patients with an acceptable toxicity profile. Recently, a Phase III study in patients with DTCs (SELECT study) demonstrated the lenvatinib efficacy in prolonging progression-free survival with respect to the placebo (18.3 vs 3.6 months; P<0.001). Although there was no statistically significant difference in the overall survival of the entire group, this result was observed when the analysis was restricted to both the follicular histotype and the group of senior patients (>65 years). The study confirmed that the most common side effects of this drug are hypertension, diarrhea, decreased appetite, weight loss, nausea, and proteinuria. In this review, we report the results of the main studies on lenvatinib efficacy in patients with advanced and progressive thyroid cancer, mainly in DTCs but also in medullary and anaplastic thyroid cancer. We also compared the efficacy of lenvatinib with that of other tyrosine kinase inhibitors, mainly sorafenib, already tested in the same type of patient population.